The Landscape of Candidemia During the Coronavirus Disease 2019 (COVID-19) Pandemic. (18th June 2021) - Seagle, Emma E; Jackson, Brendan R; Lockhart, Shawn R; Georgacopoulos, Ourania; Nunnally, Natalie S; Roland, Jeremy; Barter, Devra M; Johnston, Helen L; Czaja, Christopher A; Kayalioglu, Hazal; Clogher, Paula; Revis, Andrew; et al.
Abstract: Background: The COVID-19 pandemic has resulted in unprecedented healthcare challenges, and COVID-19 has been linked to secondary infections. Candidemia, a fungal healthcare-associated infection, has been described in patients hospitalized with severe COVID-19. However, studies of candidemia and COVID-19 coinfection have been limited in sample size and geographic scope. We assessed differences in patients with candidemia with and without a COVID-19 diagnosis. Methods: We conducted a case-level analysis using population-based candidemia surveillance data collected through the Centers for Disease Control and Prevention's Emerging Infections Program during April–August 2020 to compare characteristics of candidemia patients with and without a positive test for COVID-19 in the 30 days before their Candida culture using chi-square or Fisher's exact tests. Results: Of the 251 candidemia patients included, 64 (25.5%) were positive for SARS-CoV-2. Liver disease, solid-organ malignancies, and prior surgeries were each >3 times more common in patients without COVID-19 coinfection, whereas intensive care unit–level care, mechanical ventilation, having a central venous catheter, and receipt of corticosteroids and immunosuppressants were each >1.3 times more common in patients with COVID-19. All-cause in-hospital fatality was 2 times higher among those with COVID-19 (62.5%) than without (32.1%). Conclusions: One-quarter of candidemia patients had COVID-19. These patients were less likely to have certain underlying conditions and recent surgery commonly associated with candidemia and more likely to have acute risk factors linked to COVID-19 care, including immunosuppressive medications. Given the high mortality, it is important for clinicians to remain vigilant and take proactive measures to prevent candidemia in patients with COVID-19. Abstract : We used surveillance data to assess differences in candidemia patients with and without a prior COVID-19 diagnosis. Patients with COVID-19 and candidemia lacked established underlying conditions associated with candidemia but had twice the mortality rate versus candidemia patients without COVID-19.